POHON CITA-CITA: IMPLEMENTASI GERAKAN âSISDARLINGâ BERBASIS PENDIDIKAN KARAKTER - Nurul Majid, Dewi Yulia; Kurnia S, Ayu (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2014)
Character education is important, because it contains good moral values and be able to help children understand themselves, put themselves in a social environment and be able to support in academic achievement and non-academic. The one way to implement is sisdarling movement. Sisdarling stands for Environmentally Conscious Student that contains character education to foster positive character that focuses on the 7 characters, including: (1) love the environment; (2) Berke deity; (3) is responsible; (4) creative; (5) cooperate; (6) to be honest; (7) optimistic. The object of this program are children kelas3, 4, and 5 SD puppetry 03, Banyumanik-City Semarang.Pohon Ideals has the goal of foster positive characters to instill environmental awareness since early. Stages of implementation consists of four stages, namely the stage of program targets, dissemination, implementation and evaluation. The method used for the implementation of the program is Edufun (Education in Fun Learning). "sisdarling" movement held once a week. Each week, the children get a different material according module, which is certainly support for the formation of 7 characters sisdarling. Evaluation obtained by the observation form and interview students to the father-mother homeroom teacher 3.4, and 5 SD puppetry 03. At the end of the program, the trees are planted and cared for by the students of class 3, 4, and 5 SD 03 is expected puppetry continues to grow as one of the indicators of program success. Sustainability ideals tree is also supported by the MoU keepakatan Trees module implements Ideals in curriculum subjects KPDL (Concern In Self and the Environment)Keywords: Pohon Cita-Cita, Sisdarling, Character Education, Environment